Environmental and Economic Model of an Aircraft Accident Evaluation - NIKOLAYKIN, N. I.; NIKOLAYKINA, N. E.; SEKERIN, Vladimir Dmitriyevich; GOROKHVA, Anna Evgenevna (Journal of Environmental Management and Tourism; Vol 8 No 5 (2017): JEMT Volume VIII Issue 5(21) Fall 2017DO - 10.14505//jemt.v8.5(21).16, 2018)
Advantages of air transportation in the transport system of Russia are emphasized. An analysis of the environmental consequences of negative aircraft accidents with civil aviation aircrafts against the background of trends of the changing volume of air transportation is presented. It is shown that Russian civil aviation is described by a significant growth in traffic volumes with a slight deterioration in flight safety indicators today. It is alleged that the trend of significant growth in the volume of works is expected to continue in the future. With the obvious relevance of measures to improve flight safety, a need to significantly improve the environmental protection activities in the territory of the aircraft accident site is stated. Classification of the consequences as direct and indirect is proposed, as well as a model of the dynamics of negative impact factors. It is proposed to carry out the analysis of environmental consequences taking into consideration the theories of physical, chemical and geotechnical systems. Aircraft accidents are accompanied by the following activities: works on investigation of the causes and circumstances of the incident; works on the search and rescue of an aircraft in distress; works on rectification of the consequences, and others. It is proposed to determine the magnitude of the total damage from pollution as the size of a complex index of environmental impact, which takes the chemical, physical, biological and information components into consideration. It is found that decline in the volume of environmental costs can be achieved through carrying out the proposed preventive adjustments, which exclude the negative development of the situation to the forced critical adjustments. A methodology for calculating the necessary preventive adjustments is proposed and justified.